Simulation modeling of the dynamics of public sector human resource management system efficiency - H. Sh. B. Bakhr; S. A. Korobov (Vestnik Universiteta, 2026)
The article presents a system dynamics simulation model for forecasting the effectiveness of strategic human resource management practices in the public sector. The model is developed based on empirical data collected in 2025 in the Volgograd region (a survey of 1,250 civil servants, 45 in depth interviews, 8 focus groups, and reports from control and audit bodies). Key model variables include the integral index of HR practices, employee engagement (UWES-9), the share of appointments from the personnel reserve, and the achievement of national project KPIs. Parameter calibration is performed, and three scenarios (inertial, baseline, optimistic) are analyzed up to 2028. It is found that the inertial scenario does not move the system out of the critical zone (average integral index in 2028 – 2,32). The baseline scenario (step-by-step implementation of a set of measures) ensures an increase in the average integral index from 2,04 to 3,50 (+ 72 %), the share of appointments from the reserve from 18% to 60%, engagement from 2,9 to 4,1 points, and KPI achievement from 65 % to 82 %. Sensitivity analysis reveals the greatest influence of the speed of HR analytics implementation and top management support. The probability of achieving an average integral index > 3.0 is estimated at 0,97 (Monte Carlo method). The model can be used by regional competence centers to justify HR decisions.